2006
DOI: 10.1080/10425170600807603
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of GDF 8 (myostatin) inBos indicusandBos taurus

Abstract: We report the myostatin gene sequence of Bos indicus cattle in comparison to Bos taurus. B. indicus genomic sequence was obtained by overlapping PCR amplification of genomic DNA. Exon splice sites were confirmed by mRNA sequencing. There were 5 exonic single nucleotide polymorphisms (SNP) only one of which was a non-synonymous mutation that resulted in a serine to asparagine (S214N) amino acid substitution. The B. indicus gene has two insertions of 16 and 12 bases in the first intron. In addition, SNPs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…This insertion sequence (GAGTAGATTATGGCTT) (He et al, 2011) is the same as that reported by Tantia et al (2006).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…This insertion sequence (GAGTAGATTATGGCTT) (He et al, 2011) is the same as that reported by Tantia et al (2006).…”
Section: Resultssupporting
confidence: 56%
“…Three, 7, and 4 polymorphisms in exons 1, 2, and 3, respectively, were identified in Nellore cattle (Grisolia et al, 2009). In an analysis of the myostatin genes of Bos indicus and B. taurus, Tantia et al (2006) identified SNPs and an insertion mutation in B. indicus. Baron et al (2012) sequenced exon 2 of the myostatin gene in 332 horses of 20 different breeds and compared it against horse myostatin gene sequence deposited in GenBank.…”
Section: Introductionmentioning
confidence: 99%
“…All the mutations (nt 262, 418, 807, 869, 1045, and 1066) observed in this study were synonymous and reported previously in Qinchuan and Red Angus cattle breeds [11]. Tantia et al [27] sequenced the MSTN gene of Indian B. indicus breeds (i.e., Rathi, Deoni, Idduki, and Vatakara) and compared their sequences to B. taurus (GenBank Acc. AB076403).…”
Section: Discussionsupporting
confidence: 79%
“…Baladi goat breed sequenced under accession number KY463686 against nucleotide database showed that highly similarity with Capra hircus myostatin gene complete cds, Capra hircus breeds Guizhou Black, Jianchang Black, Angora, Shannan White, Nubian and Yichang White) myostatin MSTN gene complete cds which investigated by Liu et al [22], [23]. Also, Capra hircus breeds (Guizhou Small Xiang myostatin (MSTN) gene complete cds according to Zhu et al [6] and Guizhou Black and Qianbei Ma myostatin (MSTN) gene partial cds according to Feng et al [7], [8] and high similarity with another species like Ovis aries haplotypes 2, 3, 4, 5, 6, 7, 8, 9 and 10 myostatin (MSTN) gene, intron 1, promoter region, exon 1,5′ UTR and partial cds, Ovis aries (GDF-8) gene complete cds by Clop et al [1], Bos taurus myostatin (MSTN) gene complete cds according to Martinez et al [14] and Bos indicus myostatin gene complete cds which reported by Tantia et al [12] with identity ranged from 96 to 99% and 100% query coverage under E value (0). There were gab in one bp means that this gab may resulted according to breed variance, there were a variable identity percentage with a lot of mammals.…”
Section: Resultsmentioning
confidence: 99%